Law Reform, Justice, and Sustainable Tourism: Evaluating Legal Impacts on Hospitality Growth and Environmental Sustainability - Dewi Astutty Mochtar; Supriyadi Supriyadi; Suryaning Bawono; Kadek Wiwik Indrayanti; Eka Nugraha Putra (Journal of Law and Legal Reform, 2025)
This study evaluates 97 countries from 2012 to 2022 using a dynamic panel data approach with a threshold model, which allows for analyzing how the impact of key variables may change over time and differ across countries depending on specific conditions or thresholds This study considers the variables Total Hotel Guests, Work Participation, World Justice Project Index, and CO2 emissions. The study discovered that the quality of fair legislation significantly influences hotel performance growth, employee engagement, and environmental sustainability. The factors’ influences differ before and after attaining the World Justice Project Index threshold value, as indicated by the threshold value 1.223. When the value of the World Justice Project Index falls below the cutoff, the relationship between Total Hotel Guests and other variables is weaker. However, when the World Justice Project Index value exceeds the threshold, the relationship between Total Hotel Guests and these variables strengthens. A high World Justice Project Index reflects a strong legal system, human rights protection, and good civil justice. Countries with high World Justice Project Index values tend to attract more tourists. Work participation contributes to an increase in total hotel guests. A good World Justice Project Index creates a conducive business environment, promotes economic growth, and increases employment opportunities. Any increase in CO2 emissions will reduce the total hotel guests. A low World Justice Project Index can impact environmental quality, including air pollution. A poor environment can reduce the attractiveness of a destination and hinder tourism growth. Fair laws significantly impact the tourism and hospitality industry.